Cowpox Virus Infection in Cats: ABCD guidelines on prevention and management. Issue 7 (July 2013) - Möstl, Karin; Addie, Diane; Belák, Sándor; Boucraut-Baralon, Corine; Egberink, Herman; Frymus, Tadeusz; Gruffydd-Jones, Tim; Hartmann, Katrin; Hosie, Margaret J; Lloret, Albert; Lutz, Hans; Marsilio, Fulvio; et al.
Overview: The misnomer 'cowpox' has historical roots: cats rather acquire the virus from small rodents. It has a wide host spectrum (including man) and causes skin lesions, predominantly on the head and paws. Progressive proliferative ulcerations in kittens and immunosuppressed cats may take a fatal course. Cat owners should be informed about the zoonotic risk.